2021
DOI: 10.6066/jtip.2021.32.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Jus Bit Terfortifikasi Feso4 Instan (Jus Beefe) Dalam Menanggulangi Anemia Atlet Remaja Putri

Abstract: Prolonged physical exercise has the risk of increasing free radicals which will affect the breakdown of red blood cells and promote the risk of decreased hemoglobin. Adolescent female athletes have a risk of decreasing hemoglobin due to menstruation. This situation can get worse if the athletes have iron defi-ciency or anemia as the result of poor diet choice. Increased radicals and anemia affect the amount of oxygen carried to the tissues and the maximum volume of oxygen an individual can use to produce energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Mar'ke Bilar also contains bioactive substances that can prevent cell damage due to free radicals, including spinal cord and liver cells that produce Hb (10). The results of this study are in accordance with research conducted by Sinaga (2015), , Tombokan (2021), and Penggalih (2021), who also provided food ingredients containing anthocyanins, iron, vitamin C, and zinc (2,21,36,37).…”
Section: Hemoglobinsupporting
confidence: 90%
“…Mar'ke Bilar also contains bioactive substances that can prevent cell damage due to free radicals, including spinal cord and liver cells that produce Hb (10). The results of this study are in accordance with research conducted by Sinaga (2015), , Tombokan (2021), and Penggalih (2021), who also provided food ingredients containing anthocyanins, iron, vitamin C, and zinc (2,21,36,37).…”
Section: Hemoglobinsupporting
confidence: 90%
“…List of Ingredients (2017), is, eg, 108 mg of folic acid, 27 mg of phosphorus, 43 mg of vitamin C, 23 mg of magnesium, 9.6 mg of carbohydrates, and 1 mg of iron (10). Research conducted by Ikawati and Rokhana (2018) showed that consumption of beetroot can increase hemoglobin levels, which in Menstruating women usually have lower Hb levels (11), and also research conducted by Penggalih et al, 2021 showed that instant beet juice has the same effectiveness as commercial Fe tablets as anemia prevention for young women athletes (12). Therefore, researchers are interested in developing food formulations in other forms such as snack bars with the addition of beetroot Snack bars are one of the snacks favored by adolescents.…”
mentioning
confidence: 99%